The artist in the class struggle. A reading of «Los diarios de Emilio Renzi» (Islas, 2024)
Introduction: There are several approaches from literary criticism to the work of Ricardo Piglia; however, this paper proposes an interdisciplinary critical review for an interpretive reading of Ricardo Piglia's work, Los diarios de Emilio Renzi.Methods: Drawing from the categories outlined by Walter Benjamin around the Philosophy of History. The analysis focuses on an interdisciplinary approach where Philosophy, Literature, and History converge at a symbolic level, and Economics, Politics, and Sociology at a social level.Results: The interdisciplinary study allows for a deeper analysis of the autobiographical discourse, as it enables the observation of fiction and reality from different angles and represents the figure of the artist within the class struggle.Conclusions: In one of the possible interpretations of the narration present in the aforementioned work by Ricardo Piglia, it can be inferred that several parts of the events are established to describe the inherent responsibility of the artist in the constant social struggle.
Keywords: social criticism; philosophy of the history; interdisciplinarity; class struggle